Fabrication of 60 wt% SiO2 filled hybrid nanocomposite and its application in erosion-corrosion and radiation resistance. (July 2021) - Qi, Hong; Qian, Yuhai; Xu, Jingjun; Zuo, Jun; Li, Meishuan; Zhang, Zheng; Xie, Xiaobao; Shi, Qingshan
Abstract: Organic-inorganic hybrid nanocomposites are promising coating materials applied in hazardous space environment. The more the inorganic content is, the higher chemical passivity it has. However, the inorganic component highly filled hybrid nanocomposite increases the tendency of phase separation dramatically. To overcome this problem, we adopted easy control sol-gel method and improved mol ratio of reagents and synthesis process. The as-received epoxy-modified polysiloxane/60 wt% SiO2 hybrid coating was uniform, continuous and exhibited good adhesion and transparency. It reduced the mean erosion yield of Kapton about 2 orders of magnitude to 3.62 × 10 −26  cm 3 atom −1 and 4.16 × 10 −26  cm 3 atom −1 after AO and AO + VUV exposure, respectively. The surface characteristics and the erosion kinetic curve revealed that the performance of the as-received hybrid coating was comparable with the best existed coating systems and the hybrid coating with higher inorganic content performed better than which with lower inorganic content. According to the results and references, we concluded that the reason why the hybrid coating with attractive AO/VUV resistance was that the introduction of 60 wt% SiO2 could accelerate the formation of SiO2 layer on top of the hybrid coating, what's more, mitigate the tensile stress in the SiO2 layer. Graphical abstract: Image 1 Highlights: Overcoming the phase separation problem, a highly SiO2 filled hybrid coating is synthesized. The hybrid coating possessed better AO and VUV resistance than which with lower inorganic content. The formation of Si–O bond resulted in the effective AO erosion-corrosion resistance. The survivability of the hybrid coating is at least 3 years according to the existing space data.